Evaluation of the tail biopsy procedure on the behaviour and wellbeing of mice : a pilot study - Puustinen, Katja (SLU/Dept. of Large Animal Clinical Sciences, 2004)
Mice constitute more than half of all the laboratory animals used in the world. The use of transgenic mice has greatly increased during the last years. To determine their genetic setup a tailbiopsy is often taken and the question arises whether this is a painful procedure that requires anaesthesia and/or analgesia. The tailtip of the mouse contains bone and skin and the periosteum is well supplied with nervous tissue. Today there are no recommendations from the Swedish National Board for Laboratory Animals about anaesthesia or analgesia in conjunction with the tailbiopsy. To evaluate the effects of tail biopsy on behaviour of mice, an automatic system for behaviour recognition was used. Differences were found between these mice and control mice and these differences might be caused by pain or discomfort.